Methylmercury Export From a Headwater Peatland Catchment Decreased With Cleaner Emissions Despite Opposing Effect of Climate Warming - C. P. R. McCarter; S. D. Sebestyen; J. D. Jeremiason; E. A. Nater; R. K. Kolka (Water Resources Research)
Abstract Peatlands are sources of bioaccumulating neurotoxin methylmercury (MeHg) that is linked to adverse health outcomes. Yet, the compounding impacts of climate change and reductions in atmospheric pollutants on mercury (Hg) export from peatlands are highly uncertain. We investigated the response in annual flow‐weighted concentrations (FWC) and yields of total‐Hg (THg) and MeHg to cleaner air and climate change using an unprecedented hydroclimatic (55‐year; streamflow, air temperature, precipitation, and peatland water tables), depositional chemistry (21‐year; Hg and major ions), and streamwater chemistry (∼17‐year; THg, MeHg, major ions, total organic carbon, and pH) data sets from a reference peatland catchment in Minnesota, USA. Over the hydroclimatic record, annual mean air temperature increased by ∼1.8°C, while baseflow and the efficiency that precipitation was converted to runoff (runoff ratio) decreased. Concurrently, precipitation‐based deposition of sulfate and Hg declined, where wet Hg deposition declined by ∼3–4 μg Hg m−2. Despite declines in wet Hg deposition over the study period, the catchment accumulated on average 0.04 ± 0.01 g Hg ha−1 yr−1 based on wet Hg deposition minus THg yield alone. Annual MeHg FWC was positively correlated with mean annual air temperatures (p = 0.03, r = 0.51), runoff ratio (p < 0.0001, r = 0.76), and wet Hg deposition concentration (p < 0.0001, r = 0.79). Decreasing wet Hg deposition and annual runoff ratios counterbalanced increased peatland MeHg production due to higher air temperatures, leading to an overall decline in streamwater MeHg FWC. Streamwater MeHg export may continue to decrease only as long as declines in runoff ratio and wet Hg deposition persistently outpace effects of increased air temperature.